Developments in variable renewable energy and implications for developing countries - Arndt, Channing; Hartley, Faaiqa; Ireland, Gregory; Mahrt, Kristi; Merven, Bruno; Wright, Jarrad (Springer, 2018)
Significant and mainly unpredicted advances in variable renewable energy technologies are resulting in structural shifts in energy systems globally causing an energy revolution. This review focuses on the implications for developing countries including the water-energy nexus.